2008
DOI: 10.1371/journal.pone.0002782
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Serotonin Transporter Function during Fetal Development Causes Dilated Heart Cardiomyopathy and Lifelong Behavioral Abnormalities

Abstract: BackgroundWomen are at great risk for mood and anxiety disorders during their childbearing years and may become pregnant while taking antidepressant drugs. In the treatment of depression and anxiety disorders, selective serotonin reuptake inhibitors (SSRIs) are the most frequently prescribed drugs, while it is largely unknown whether this medication affects the development of the central nervous system of the fetus. The possible effects are the product of placental transfer efficiency, time of administration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
3
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 33 publications
12
139
3
9
Order By: Relevance
“…Continuous infusion of fluoxetine in sheep via maternal femoral vein catheter yielded concentrations in maternal and fetal serum of ;150 and ;60 ng/ml, respectively; no measurements of norfluoxetine were obtained (Morrison et al, 2004). Similar results were found in mice: placental transfer of fluoxetine was 69%, whereas human placental transfer is 73% (Noorlander et al, 2008). Placental transfer comparing rodents and humans is also reported for fluvoxamine (30% in mice, 35% in humans).…”
Section: Selective Serotonin Reuptake Inhibitor Antidepressant Anisupporting
confidence: 55%
See 3 more Smart Citations
“…Continuous infusion of fluoxetine in sheep via maternal femoral vein catheter yielded concentrations in maternal and fetal serum of ;150 and ;60 ng/ml, respectively; no measurements of norfluoxetine were obtained (Morrison et al, 2004). Similar results were found in mice: placental transfer of fluoxetine was 69%, whereas human placental transfer is 73% (Noorlander et al, 2008). Placental transfer comparing rodents and humans is also reported for fluvoxamine (30% in mice, 35% in humans).…”
Section: Selective Serotonin Reuptake Inhibitor Antidepressant Anisupporting
confidence: 55%
“…These findings were noted to be strongly indicative of pulmonary hypertension (Fornaro et al, 2007). Noorlander et al (2008) also reported that mice prenatally exposed to fluoxetine manifested decreased left ventricle wall thickness, a measure of dilated cardiomyopathy, on PND20 and 90. These findings provide some concordant data regarding persistent pulmonary hypertension reported in the clinical population.…”
Section: F Cardiovascular Outcomesmentioning
confidence: 89%
See 2 more Smart Citations
“…In the UK antidepressant prescribing during pregnancy increased fourfold from 1992 to 2006, with Selective Serotonin Reuptake Inhibitors (SSRIs) most often chosen 5 . SSRIs cross the human placenta, with fetal levels varying according to treatment type 6,7 and are found in amniotic fluid 8 . The significance of prenatal exposure to SSRIs and outcomes in terms of the physical health and the neurodevelopment of the infant and child remain unclear.…”
Section: Introductionmentioning
confidence: 99%